Ответ(ы) на вопрос:
[latex] \frac{5}{4+ \sqrt{11} }+ \frac{8}{ \sqrt{19}- \sqrt{11} }- \frac{10}{ \sqrt{19}+3 } [/latex]
Избавимся от иррациональности в знаменателе каждой дроби:
[latex] \frac{5(4-\sqrt{11})}{(4+ \sqrt{11})(4- \sqrt{11}) }+ \frac{8(\sqrt{19}- \sqrt{11} )}{ (\sqrt{19}- \sqrt{11})(\sqrt{19}- \sqrt{11} ) }- \frac{10(\sqrt{19}+3)}{ (\sqrt{19}+3)(\sqrt{19}+3) }= \\ =\frac{5(4-\sqrt{11})}{(16-11) }+ \frac{8(\sqrt{19}- \sqrt{11} )}{ (19-11)}- \frac{10(\sqrt{19}+3)}{ (19-9)}= \\ =\frac{5(4-\sqrt{11})}{5 }+ \frac{8(\sqrt{19}- \sqrt{11} )}{ 8}- \frac{10(\sqrt{19}+3)}{10}= \\ =4-\sqrt{11}+\sqrt{19}- \sqrt{11}-\sqrt{19}-3=1[/latex]
Не нашли ответ?
Похожие вопросы